Direct and indirect photodynamic therapy effects on the cellular and molecular components of the tumor microenvironment - Milla Sanabria, Laura Natalia (2012)
Photodynamic therapy (PDT) is a novel cancer treatment. It involves the activation of a photosensitizer (PS) with light of specific wavelength, which interacts with molecular oxygen to generate singlet oxygen and other reactive oxygen species (ROS) that lead to tumor cell death. When a tumor is treated with PDT, in addition to affect cancer cells, the extracellular matrix and the other cellular components of the microenvironment are altered and finally this had effects on the tumor cells survival. Furthermore, the heterogeneity in the availability of nutrients and oxygen in the different regions of a tridimensional tumor has a strong impact on the sensitivity of cells to PDT. In this review, we summarize how PDT affects indirectly to the tumor cells, by the alterations on the extracellular matrix, the cell adhesion and the effects over the immune response. Also, we describe direct PDT effects on cancer cells, considering the intratumoral role that autophagy mediated by hypoxia-inducible factor 1 (HIF-1) has on the efficiency of the treatment.